Gender-related impact on outcomes of high density lipoprotein in acute ST-elevation myocardial infarction. (August 2016) - Distelmaier, K.; Schrutka, L.; Wurm, R.; Seidl, V.; Arfsten, H.; Cho, A.; Manjunatha, S.; Perkmann, T.; Strunk, G.; Lang, I.M.; Adlbrecht, C.
Abstract: Background and aims: There is rising evidence that cardioprotective functions of high-density lipoprotein (HDL) have significant impact on clinical outcomes. ST-elevation myocardial infarction (STEMI) represents a high-risk vascular condition. Whether higher HDL-cholesterol concentrations in women correspond to protective anti-oxidant properties in the setting of STEMI is unknown. Methods: We prospectively assessed gender related differences in the anti-oxidant function of HDL, and the impact of HDL properties on mortality in 242 women and men with STEMI. Blood samples to determine HDL function and sex hormone levels were collected during primary percutaneous coronary intervention. Results: Patients were stratified according to preserved anti-oxidant HDL function (HDL oxidant index (HOI) < 1) and pro-oxidant HDL (HOI≥1). Despite higher serum levels of HDL-cholesterol in postmenopausal women (48 mg/dl, IQR 42–54, versus 39 mg/dl, IQR33-47, p  < 0.001 in men), the proportion of patients with pro-oxidant HDL was not different between women (35%) and men (46%, p  = 0.132). Kaplan–Meier analysis revealed higher cardiovascular mortality in both women ( p  = 0.021) and men ( p  = 0.045) with pro-oxidant HDL. We identified pro-oxidant HDL as strong and independent predictor of cardiovascular mortality with an adjusted HR of 8.33 (95% CI, 1.55–44.63; p  = 0.013) in women and with an adjusted HR of 5.14 (95% CI, 1.61–16.42; p  = 0.006) in men. Higher levels of free sex hormones (estradiol and testosterone) were associated with pro-oxidant HDL. HDL-cholesterol levels showed no association with mortality (HR in women 1.03, 95% CI 0.96–1.11, p  = 0.45 and HR in men 0.99, 95% CI 0.94–1.05, p  = 0.72). Conclusions: Total HDL-cholesterol serum levels were not associated with mortality in STEMI patients. Pro-oxidant HDL was a strong and independent predictor of mortality in women and men with STEMI. The present study provides a link between sex hormones, HDL function and clinical events in STEMI patients. In clinical practice and future clinical trials, anti-oxidant properties of HDL rather than total HDL serum levels should be used for risk stratification. Highlights: Anti-oxidant capacity of HDL is independent of serum levels and does not differ between postmenopausal women and men. Anti-oxidant capacity of HDL is a significant predictor of mortality in male as well as female patients with STEMI. Higher levels of free sex hormones were associated with pro-oxidant HDL.